Etos Kerja dalam Kinerja Karyawan Generasi Z di Daerah Khusus Ibukota Jakarta - Edinna, Melfin; Anfas, Anfas (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
The study aims to explore work ethic on employee performance in generation Z in the Special Capital Region of Jakarta. SPSS for Windows version 24 as software to analyse the sample data in this study. The data used in the study is a work ethic scale with a population and sample of 100 people with a birth period of 1995 to 2015. The method applied is simple linear regression through partial (t) test with the independent variable, namely work ethic and the dependent variable, namely employee performance. The study results show that work ethic cannot affect the improvement of the performance of generation Z employees in the Special Capital Region of Jakarta and work ethic on employee performance in generation Z in the Special Capital Region of Jakarta has a negative effect and is normally distributed